Shopping trip frequency and duration in Canada: An analysis of personal trends based on the General Social Surveys of 1998 and 2005 - Bonin, Julien (My University, 2008)
Shopping is an essential aspect of our day to day lives, as it is necessary in order to fulfill numerous needs and desires. Evidence suggests that the proportion of travel for retail and service is increasing, such that traffic congestion can no longer simply be attributed to work related travel. The restructuring of the commercial sector and automobility has increased competition between outlets, such that stores are now competing against merchants across a large spatial region. As a consequence, many consumers are required to travel long durations to accomplish shopping activities.
Discrete/continuous models can determine the likelihood that an individual will engage in a shopping activity, followed by the analysis of the travel duration. The models can overcome the sample-selectivity bias, since shopping is only accomplished by a subsample. Traditionally, the models have been estimated disjointly, however, they are increasingly being estimated jointly.
Using the General Social Survey, the objectives of this study are twofold. First,
the study aims to analyze the shopping frequency and travel duration of Canadians by
comparing the one day behaviour of residents of non-Census Metropolitan Areas (non-CMA) and Census Metropolitan Areas (CMA) for 1998 and 2005. Second, it will
investigate the potential of a newly developed discrete/continuous model for the joint
analysis of shopping travel behaviour. The results of the analysis suggest that shopping
travel behaviour is similar regardless of region, and that the joint model provided
consistent and realistic estimates.
Keywords: Earth Sciences; Geography; Earth Sciences